Rural Tourism 3.0: Conceptualising An Innovative Approach In Monitoring The ‘Health’ Of Rural Destinations In Malaysia - Vikneswaran, Nair; Badaruddin, Mohamed; Amran, Hamzah; Lo, May-Chiun; Hong, Jer Lang (BIMP-EAGA, 2014)
With the evolution from Web 1.0 to Web 3.0, web servers are able to dynamically generate rich web information to internet users. The capabilities of Web 3.0 can be used in the tourism sector to manage the industry more effectively. One of the major forms of tourism that is gaining its momentum in Malaysia and requires efficient management is rural tourism. Nonetheless, in the last decade, the concept of rural tourism has melded with mainstream tourism and resulting in it losing its distinctness. Consequently, the tourism industry's growth throughout the years has created an increasing amount of stress economically, socially and environmentally. Hence, the development of a sustainable and responsible rural tourism is needed in fulfilling the objectives of all stakeholders in the system. Thus, the main aim of this paper is to conceptualise a framework to monitor the ‘health’ of rural tourism destinations in Malaysia using Web 3.0 technologies. A rural tourism prototype called the “Rural Tourism 3.0” is developed to assess, advice and monitor the economic, socio-cultural and environmental responsible impact of rural tourism destinations using an integrated real-time decision support system.